NUTRITION EDUCATION IN ALPHA GENERATION TO ACHIEVE OPTIMAL GROWTH AND DEVELOPMENT - Arina Zulva Maulida; Muh Syauqi Malik (UPI Kampus Cibiru, 2021)
Alpha generation requires nutritional education to achieve optimal growth and development. This research aims to provide nutritional education to the alpha generation to achieve optimal growth and development. Method used by researchers is descriptive qualitative literature studies. The authors see a significant correlation between nutrition education and changes in children's behavior in responding to their food dishes. The more nutritional education obtained, the more children will realize the importance of food so that it is more devoured in eating food. References taken by authors are sourced from the author's personal experience as a Nutritionist supported by scientific publications such as reputable national journals, books, websites, and various relevant research sources. The subjects in this study were children aged 0 to 8 years. The results showed that generation alpha is the first generation to hold individuals born in the 21st century who have the characteristics of more believe in social media, prefer to shop online, Rarely make physical contact in communicating, do not like excessive consumption, and repeat the same for pleasure. Wrong nutritional behaviors in elementary school-aged children include not eating a balanced dietary menu, not breakfast, unhealthy snacks, consuming Junk Food and Fast Food, and consuming sugar in excess. Some methods of nutrition education that can be practised in the alpha generation are education in the form of interventions, education using cards, and android-based education.